The Effect of Pricing Strategy, Promotional Activities, Market Research, and Supply Chain Management on Marketing Performance in Indonesian Start-ups - Wijayanto, Gatot; Rama, Rovanita; Jushermi, Jushermi; Pramadewi, Arwinence; Rivai, Yutiandry; S, Deswita (International Journal of Business, Law, and Education, 2024)
The present study examines the complex relationships that exist between pricing strategy, promotional activities, supply chain management, market research, and marketing performance within the framework of start-ups in Indonesia. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to assess data from a sample of 150 start-ups quantitatively. The findings demonstrate the interdependence of strategic choices and their influence on marketing results by pointing out important correlations between these variables. Key factors influencing marketing performance were found to be pricing strategy, advertising, supply chain management, and market research. The results offer practical advice for aspiring business owners, highlighting the significance of comprehensive and integrated marketing approaches for long-term success in the cutthroat market.